Imaging in Autoimmune Neurology - Linnoila, Jenny J. (Seminars in Neurology, 2018)
Autoimmune disorders are becoming increasingly recognized within the broader field of neurology. The discovery of multiple, novel, neutrally targeted autoantibodies over the past decade and their translation into commercially available testing, in particular, has aided in the more rapid diagnosis of these disorders. When considering imaging in autoimmune neurologic disorders, it is important, when possible, to visualize the autoimmune process itself, as well as to make sure that the patient does not have an associated malignancy driving the overall process. Positron emission tomographic scans can aid in the detection of small tumors with limited spread, as well as in the visualization of autoimmune processes affecting the brain and/or spinal cord. In autoimmune disorders of the central nervous system, imaging abnormalities can appear within the limbic system, extralimbic areas, and spinal cord. Such imaging abnormalities can serve as objective markers to follow over time to assess patients' responses to treatment. It is important to recognize that overlapping syndromes (for instance, both demyelinating and autoimmune or both infectious and autoimmune) exist and that inflammatory disorders can leave behind sequelae that can be recognized on subsequent imaging. Work is currently underway to develop more specific imaging techniques for autoimmune neurologic disorders.
Keywords: imaging; paraneoplastic; autoimmune; encephalitis; spinal cord